2021
DOI: 10.1007/s13201-021-01466-6
|View full text |Cite
|
Sign up to set email alerts
|

Small hydropower dam site suitability modelling in upper Benue river watershed, Nigeria

Abstract: Small hydropower (SHP) is one of the most critical renewable energy that is well adapted to the rural localities in less developed countries across the world. Most rural communities in Nigeria are off the national power grid and are bedevilled by an inconsistent supply of electricity. The one possible panacea to the rural energy crisis is harnessing the terrain and abundant rivers and streams within their domain. This study aimed to identify and select suitable sites for the SHP dam in the upper Benue river wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In another similar study, in addition to the method in this study, the analytical hierarchy process (AHP) was used as a selection tool in the selection of potential sites in Nigeria. (Odiji et al, 2021). Although theoretical calculations have been made for the determination of hydropower potential areas with the help of GIS in different studies, comparisons with existing hydropower plants have not been made, as was done in this study Zaidi & Khan, 2018;Setiawan, 2015).…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…In another similar study, in addition to the method in this study, the analytical hierarchy process (AHP) was used as a selection tool in the selection of potential sites in Nigeria. (Odiji et al, 2021). Although theoretical calculations have been made for the determination of hydropower potential areas with the help of GIS in different studies, comparisons with existing hydropower plants have not been made, as was done in this study Zaidi & Khan, 2018;Setiawan, 2015).…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…The application of GeoDetector and RFE-RF for influencing variable selection involves binary classification, where data representing MHP sites are labeled as '1' and non-MHP sites are labeled as '0'. Due to several studies confirming that MHP sites are not suitable in the river with >45% slope [25], the non-MHP sites were determined at about 1,000 m downstream from existing MHP sites with >45% slope. This study used a 1:1 ratio between MHP site data and non-MHP site data to obtain 216 non-MHP sites.…”
Section: Data Source and Processingmentioning
confidence: 99%
“…A recent analysis found that the state's ability to implement hydropower schemes is limited by the lack of inland water and flooded land areas. Nonetheless, the research suggested using run-off-river systems to generate electricity in places like these using micro and pico turbines [29,30].…”
Section: Waste-to-energymentioning
confidence: 99%